2009
DOI: 10.1002/ajhb.20899
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory sympathetic nervous system activity and diet‐induced waist‐circumference reduction in obese Japanese women

Abstract: The present study is designed to investigate how and to what extent sympathovagal behavior in a balanced low-calorie diet relates to favorable changes of body mass, waist circumference, and/or metabolic risk factors. The study involved 28 mildly obese women without clinical complications, who underwent an 8-week calorie restriction program using a 1,200-kcal daily diet with an adequate nutrient content; including two regular meals, and one formula meal replacement. All subjects were examined before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…30 Anthropometric data were used to determine the body mass index [BMI: body weight (in kg) divided by height (in m) squared] and the waist-hip ratio [waist (in cm) divided by hip (in cm)]. [29][30][31] For measurement of body fat and lean mass, the bipolar impedance of the upper limbs (OMRONÒ, Kyoto, Japan) 31 was performed, and the participants were instructed not to exercise, not to use metals in the body, and to maintain normal hydration status.…”
Section: Body Composition Assessmentmentioning
confidence: 99%
“…30 Anthropometric data were used to determine the body mass index [BMI: body weight (in kg) divided by height (in m) squared] and the waist-hip ratio [waist (in cm) divided by hip (in cm)]. [29][30][31] For measurement of body fat and lean mass, the bipolar impedance of the upper limbs (OMRONÒ, Kyoto, Japan) 31 was performed, and the participants were instructed not to exercise, not to use metals in the body, and to maintain normal hydration status.…”
Section: Body Composition Assessmentmentioning
confidence: 99%
“…The very low frequency band (0.001-0.04 Hz) has been considered by the Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology (1996) guidelines to be too small to be a reliable indicator during short-term recordings. However, recent investigations have challenged this assertion (Nagai et al, 2005;Nagai et al, 2006;Fujibayashi et al, 2009) and we have found that 5-min recordings produced VLF measurements that represented a significant proportion (23%-52%) of the total heart rate spectral power expressed in normalized units. The present study was designed, partly, to test the physiological significance of the very low frequency band as an indicator of sympathetic thermoregulatory and metabolic energy signaling.…”
Section: Heart Rate Variability Analysesmentioning
confidence: 86%
“…The guidelines for standardizing heart rate variability measurements state that the very low frequency spectral power may represent too small a proportion of the total spectral power to be worthy of analysis during short intervals of electrocardiographic recordings (Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology 1996). More recent studies have suggested that the very low frequency power could, under appropriate conditions, be an indicator of sympathetic thermoregulatory and metabolic energy signaling (Nagai et al, 2005;Nagai et al, 2006;Fujibayashi et al, 2009). The significant positive correlation between body temperature and very low frequency power that we found during fasting, but not during paced breathing, corroborates the previous reports of a thermoregulatory and metabolic energy signaling function of the very low frequency band.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomical landmarks to measure the circumference (cm), in the upright position of the body were: 1) waist: measured at the above the iliac crest; 2) hip: measured at the largest protuberance of the buttocks [12]. The body fat and lean mass were measured by the bipolar electrical bioimpedance of the upper limbs (OMRON®, Kyoto, Japan) [13]. The measurements of the skinfolds (in mm) were performed in the upright position, the caliper was placed at specific locations on the right side of the body, which was relaxed and dry.…”
Section: Assessment Of Body Composition and Skinfoldsmentioning
confidence: 99%